Dnmt2 methyltransferases and immunity: An ancient overlooked connection between nucleotide modification and host defense? - Durdevic, Zeljko; Schaefer, Matthias R. (Bioessays, 2013)
Many species maintain cytosine DNA methyltransferase (MTase) genes belonging to the Dnmt2 family. Prokaryotic modification-restriction systems utilize DNA methylation to distinguish between self and foreign DNA, and cytosine methylation in eukaryotic DNA contributes to epigenetic mechanisms that control gene expression. However, Dnmt2 proteins display only low or no DNA MTase activity, making this protein family the odd and enigmatic family member. Recent evidence showed that Dnmt2 proteins are not DNA but RNA MTases with functions in biological processes as diverse as stress responses and RNA-mediated inheritance. These observations not only raise profound questions regarding the perceived substrate specificities of cytosine MTase, but also suggest links between DNA and RNA modification systems. Here, we speculate that Dnmt2 proteins might be part of an ancient cytosine modification toolbox that is used to successfully respond to environmental challenges, including constantly evolving RNA and DNA substrates.
Gesehen am 05.01.2021